The Molecular Mechanisms and Therapeutic Potential of Cranberry, D-Mannose, and Flavonoids against Infectious Diseases: The Example of Urinary Tract Infections - Petros Ioannou; Stella Baliou (MDPI AG, 2024)
The treatment of infectious diseases typically includes the administration of anti-infectives; however, the increasing rates of antimicrobial resistance (AMR) have led to attempts to develop other modalities, such as antimicrobial peptides, nanotechnology, bacteriophages, and natural products. Natural products offer a viable alternative due to their potential affordability, ease of access, and diverse biological activities. Flavonoids, a class of natural polyphenols, demonstrate broad anti-infective properties against viruses, bacteria, fungi, and parasites. Their mechanisms of action include disruption of microbial membranes, inhibition of nucleic acid synthesis, and interference with bacterial enzymes. This review explores the potential of natural compounds, such as flavonoids, as an alternative therapeutic approach to combat infectious diseases. Moreover, it discusses some commonly used natural products, such as cranberry and D-mannose, to manage urinary tract infections (UTIs). Cranberry products and D-mannose both, yet differently, inhibit the adhesion of uropathogenic bacteria to the urothelium, thus reducing the likelihood of UTI occurrence. Some studies, with methodological limitations and small patient samples, provide some encouraging results suggesting the use of these substances in the prevention of recurrent UTIs. While further research is needed to determine optimal dosages, bioavailability, and potential side effects, natural compounds hold promise as a complementary or alternative therapeutic strategy in the fight against infectious diseases.